Tokovi okroglega lesa in lesnih ostankov v Sloveniji - Krajnc, Nike (Zbornik gozdarstva in lesarstva, 2006)
The main objective of the study was to make a model that identifi es fl ows and use of roundwood and wood wastes in Slovenia in the basic year. A new conceptual model was created. On the basis of this model, two roundwood and one wood waste balance were prepared. A wide range of available data was takeninto consideration, the quality of data evaluated and a proposal for improving their quality prepared. The results of roundwood balance showed a defi cit of 536,000 m3, if offi cial data for annual removals were taken intoaccount. In the case of modelled (enlarged) removals, the roundwood balance is positive. The use of 297.000 t of wood wastes in wood wastes balance remains unknown. The gathered data have limited applicability and needto be improved. Wood fl ow and data analysis should play an important role as part of strategic planning and decision making at the sectoral, local,regional and national levels.
Keywords: bilance; izkoristek; izvoz; lesni ostanki; okrogli les; raba; Slovenia; Slovenija; uvoz